Defining the effective clinical preceptor: a conceptual framework for role modeling in medical education - Xavier, Flaviana Cardoso; Feitosa, Elaine Saraiva; de Melo Cunha, Silvia; do Carmo Sá, Henrique Luis (Frontiers in Education, 2026)
BackgroundRole modeling by clinical preceptors is a critical component in the professional development of medical students, yet the attributes and contextual factors that contribute to preceptor effectiveness as role models remain underexplored. This study aimed to design a conceptual framework to better understand and enhance the effectiveness of clinical preceptors as professional models in medical education.MethodsA four-stage, mixed methods, sequential explanatory design was employed. First, a literature review informed the development of a survey instrument focused on attributes of effective clinical preceptors. Second, a survey was administered to fifth- and sixth-year medical students and clinical preceptors at a medical school in Brazil, collecting perceptions of positive and negative preceptor attributes. Third, responses were analyzed and grouped by similarity and frequency. Finally, a conceptual framework was developed using a design thinking process, integrating survey findings and theoretical perspectives.ResultsA total of 222 participants (173 students and 49 preceptors) were surveyed, yielding 1,130 citations of attributes, resulting in the identification of 90 distinct attributes of effective preceptors. The most valued attributes included knowledge, empathy, didactics, patience, availability, kindness, willingness to teach, respect, and humility. These attributes were synthesized into a conceptual framework comprising three domains—contextual, subjective, and experiential—highlighting the interplay of intrinsic and extrinsic factors in preceptor effectiveness as role models.ConclusionThe proposed framework provides a comprehensive approach to understanding the effectiveness of clinical preceptors as role models. It offers practical guidance for faculty development, curriculum planning, and further research on role modeling in medical education, with potential to enhance both teaching quality and professional identity formation among students.